Breed and management system effects on feedlot performance and carcass traits - D.T. Hickok; R.R. Schalles; D.E. Franke; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1991)
Eighty nine steers with different proportions of Angus, Hereford, Charolais, Brahman, and Gelbvieh breeding from rotational and terminal crossbreeding systems were produced in Louisiana and finished at KSU. Half of each breed group was placed in the feedlot at weaning (calves) and the other half as yearlings. Half of the each group was slaughtered at a low (0.3-0.4 in.), and the other half at high (0.5 - 0.6 in.) fat thickness. As percentage of Charolais and Gelbvieh breeding increased, feedlot performance improved. As percentage of Charolais, Gelbvieh, and Angus increased, carcass desirability improved. Steers started on feed at weaning were more efficient in feed conversion and were more profitable than those started as yearlings. Age did not affect carcass marbling or quality grade.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Cattle; Breeds; Management; Performance; Carcass; Returns